Inflammasomes in Atherosclerosis-From Pathophysiology to Treatment - Panagiotis Theofilis; Evangelos Oikonomou; Christos Chasikidis; Konstantinos Tsioufis; Dimitris Tousoulis (MDPI AG, 2023)
Atherosclerosis, a chronic inflammatory disease characterized by arterial plaque accumulation, remains a significant global health challenge. In recent years, inflammasomes, the intracellular multiprotein complexes crucial for initiating innate immune responses, have emerged as key players in atherosclerosis pathophysiology. This review article aims to provide a comprehensive overview of the current understanding of inflammasome activation and its impact on atherosclerosis development and progression. We explore the intricate interplay between traditional cardiovascular risk factors and inflammasome activation, leading to the perpetuation of inflammatory cascades that drive plaque formation and instability. The review focuses on the molecular mechanisms underlying inflammasome activation, including the role of pattern recognition receptors and cytokines in this process. Moreover, we discuss the contribution of inflammasomes to endothelial dysfunction, foam cell formation, and vascular inflammation. Additionally, recent advances in therapeutic strategies targeting inflammasomes are examined, including pharmacological agents and potential immunomodulatory approaches. By collating and analyzing the current evidence, this review provides valuable insights into the potential of inflammasome-targeted therapies for atherosclerosis management and treatment. Understanding the pivotal role of inflammasomes in atherosclerosis pathophysiology offers promising prospects for developing effective and personalized therapeutic interventions that can mitigate the burden of this prevalent cardiovascular disorder and improve patient outcomes.